Facilitation as a component of evidence implementation: a multinational perspective. Issue 3 (10th September 2022) - Lizarondo, Lucylynn; McArthur, Alexa; Moola, Sandeep; Albornos-Muñoz, Laura; Badeaux, Jennifer; Bennett, Marsha; Püschel, Vilanice Alves de Araújo; González-Monasterio, Emilia Irene; Mwita, Clifford; Perrenoud, Beatrice; Porche, Demetrius; Rodrigues, Rogério; et al.
ABSTRACT: Background: Facilitation is a key component of JBI's approach to evidence implementation along with context analysis and evaluation of process and outcomes. Although the role of facilitation is recognized as a critical component of evidence implementation, what constitutes effective facilitation is poorly understood. Aim: This article presents a descriptive exploration of facilitation as it occurs in evidence implementation initiatives conducted in various healthcare and geographical contexts. All projects used the JBI approach to evidence implementation. Methods: To provide a multinational perspective on how facilitation was operationalized to promote positive changes in clinical practice and health outcomes, five case studies of evidence implementation projects are presented. Results: The cases highlighted that facilitation is a multifaceted process that can be met through a variety of roles that address aspects of education and capacity building, partnerships, action planning, problem solving and evaluation. Facilitation in all cases appeared to be collaborative, with multiple 'players' within and outside of the health organization being involved in the process. Although there are similarities in activities, facilitation involved some level of local contextualization where there were unique or additional activities performed to accommodate the local needs and requirements of the health organization involved in each case. Numerous contextual factors influenced the success of the implementation initiative. Conclusion: The cases emphasized the complex nature of facilitation as a strategy for evidence implementation, indicating that contextual attributes and features define the range of knowledge, skills, and activities that should take place in order for facilitation to be effective. Although there appears to be some core components, tailoring and adaptation of the facilitation process (or roles) is required.